CHARACTERISTICS OF IRONY AS A PRODUCT OF SPEECH ACTIVITY IN ENGLISH AND UZBEK LANGUAGES - Dilfuza Sultanmuratova; M. Ergashov (Journals Park Publishing, 2022)
Due to the fact that irony is one of the stylistic device which is used for ensuring effective intercultural communication. Teaching English language is easier to explain if a teacher gives various irony in mother tongue and  depicted  in L2. The article is devoted to characterize the irony giving some relevant example.
Keywords: Irony, ironic interpretation , reality, ground-breaking finding, implicature.